Vascular risk factors and carotid atheromatous disease in patients over 65 years of age - Mateus, Sónia; de Mina, Vanda Pós; Coelho, Patrícia; Rodrigues, Francisco; Mendes, Irene (Journal of Cardiovascular Medicine and Cardiology, 2023)
Introduction: Vascular risk factors are decisive in the evolution of atherosclerotic disease and the carotid and vertebral Doppler ultrasound allows monitoring its onset and progress. The measurement of arterial wall thickening allows the early diagnosis of the disease enhancing its treatment and control of vascular risk factors. Aim: Analysing the presence of atheromatous disease in individuals aged > 65 years and understanding its correlation with vascular risk factors. Materials and methods: This is a cross-sectional observational study, in individuals aged > 65 years and underwent carotid echoDoppler between January 1, 2012, and December 31, 2021. The intimal-media index was calculated, as was the presence of atheromatous plaques, their hemodynamic repercussion and vascular risk factors were recorded. Results: A sample of 5885 individuals was obtained with 41.8% female and 58.2% male. The mean age was 76.59 (± 6.69), with a range between 65 and 98 years. Arterial hypertension was the most prevalent 81.3%. There was a significant positive relationship between the intima-media index and age (p = 0.001). In the presence of plaques, male gender, arterial hypertension, diabetes, dyslipidemia, and smoking it presents a positive correlation. Conclusion: In this sample, non-modifiable vascular risk factors seem to be determinants in the presence of increased arterial wall thickness. In the presence of signs of a more advanced stage of atherosclerotic disease, modifiable vascular risk factors are decisive, corroborating the already-known importance of strict control over them for their treatment.